2016 IEEE International Conference on Big Data (Big Data) 2016
DOI: 10.1109/bigdata.2016.7840595
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of big data quality: An empirical examination in financial service organizations

Abstract: Abstract-Big data has been acknowledged for its enormous potential. In contrast to the potential, in a recent survey more than half of financial service organizations reported that big data has not delivered the expected value. One of the main reasons for this is related to data quality. The objective of this research is to identify the antecedents of big data quality in financial institutions. This will help to understand how data quality from big data analysis can be improved. For this, a literature review w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…In addition, data quality also should be considered in big data analysis. Fardani Haryadi, Hulstijn, Wahyudi, van der Voort, and Janssen (2016) defined data quality of different banks and proposed detailed goals. Brammertz and Mendelowitz (2014) proposed an information extraction for financial regulation from financial big data which comes from the granularity information of financial contracts, transformed into a contingent cash flow and they also developed a mixed model for multi-level financial objectives such as institutions, systems and individuals.…”
Section: Data Challenges In Financial Riskmentioning
confidence: 99%
“…In addition, data quality also should be considered in big data analysis. Fardani Haryadi, Hulstijn, Wahyudi, van der Voort, and Janssen (2016) defined data quality of different banks and proposed detailed goals. Brammertz and Mendelowitz (2014) proposed an information extraction for financial regulation from financial big data which comes from the granularity information of financial contracts, transformed into a contingent cash flow and they also developed a mixed model for multi-level financial objectives such as institutions, systems and individuals.…”
Section: Data Challenges In Financial Riskmentioning
confidence: 99%
“…Likewise, Lakshen et al [50] argued on the various technical challenges that must be addressed before the potential of BDT and DQD can be fully realised. Haryadi et al [14] confirmed that BDT and DQD are the central issues for implementing BDA.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Meanwhile, the concept of information quality is defined as how well the information supports the task [46]. Haryadi et al [14] asserted that data quality is focused on data that have not been analysed, while information quality is focused on the analysis that has been done on the data. This study, however, opines that data quality should focus on the wellness and appropriateness of data, which encompasses either before or after it has been analysed, in which it should meet the requirements of organisations [12].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations